Size at maturity and length-weight relationships of the blurred lantern shark Etmopterus bigelowi (Squaliformes: Etmopteridae) caught off southeastern Brazil - Mourato, B. L. (2018)
The blurred lantern shark Etmopterus bigelowi, a deep-water squaloid shark, is globally widespread in temperate and tropical waters, but there is little available information about its biology owing to its relative rarity of capture and taxonomic confusion with its sibling species Etmopterus pusillus. Specimens used in this study were collected from July to December 2004 as by-catch in the commercial deep-water trawl fishery targeting red shrimp Aristaeomorpha foliacea in the southwestern Atlantic. We examined 55 specimens (22 males and 33 females) ranging in total length (TL) from 31.5 to 73 cm and in total weight from 103 to 1600 g. Length-weight relationships were explored for each sex and significant differences were found in the slope coefficients of the male and female regressions. The size at maturity for each sex was evaluated fitting a logistic regression. Females matured at larger sizes than males, with estimated sizes at first maturity of 56.0 cm TL for females and 45.1 cm TL for males. The present study provides important preliminary information about E. bigelowi that can be incorporated in risk assessment and stock assessment models, essential for efficient management practices aimed at avoiding overexploitation of these vulnerable deep-sea sharks.